2013
DOI: 10.1177/1753193413504160
|View full text |Cite
|
Sign up to set email alerts
|

Primary excision of the ulnar head for fractures of the distal ulna associated with fractures of the distal radius in severe osteoporotic patients

Abstract: We performed primary excision of the ulnar head on 23 patients over 70 years of age with severe comminuted fractures of both the distal radius and ulna. The distal radius fracture was fixed rigidly with a volar locking plate, and the ulnar head was resected at the fracture site. All the distal radial fractures united without major complications. The mean wrist flexion/extension arc was 122°, the mean pronation/supination arc was 164°, and grip strength was 69% of that on the contralateral side. All patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Several surgical treatment methods have been reported for distal metaphyseal ulnar fractures accompanied by distal radius fractures, such as the conventional plate, 2 locking plate, 3 , 4 hook plate, 5 - 7 intramedullary device, 8 , 9 and primary resection. 10 Fixation of distal metaphyseal ulnar fractures can be challenging, 11 and several studies have shown the validity of conservative treatment alternatives. 12 - 17 If clinical outcomes of the conservative treatment for distal metaphyseal ulnar fractures accompanying distal radius fractures are the same when compared with those of surgical fixation, there is a possibility that unnecessary surgery can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical treatment methods have been reported for distal metaphyseal ulnar fractures accompanied by distal radius fractures, such as the conventional plate, 2 locking plate, 3 , 4 hook plate, 5 - 7 intramedullary device, 8 , 9 and primary resection. 10 Fixation of distal metaphyseal ulnar fractures can be challenging, 11 and several studies have shown the validity of conservative treatment alternatives. 12 - 17 If clinical outcomes of the conservative treatment for distal metaphyseal ulnar fractures accompanying distal radius fractures are the same when compared with those of surgical fixation, there is a possibility that unnecessary surgery can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…In a reported study no patients found their activities disturbed by reduced grip strength. Long term follow-up of almost 2 years in this series showed gradual improvement in the grip power [5]. With the accurate indication and diligent surgical workmanship, the classical Darrach distal ulna resection can be extended as an indispensable procedure when there is failure to achieve anatomic restoration of the ulna head to sigmoid notch articular relationship, compounded with unhealthy ulna bone and soft tissue scarcity.…”
Section: Discussionmentioning
confidence: 71%
“…More recently, Yoneda and Watanabe 25 reported the results of a case series of 23 patients aged over 70 years (mean 80 years) who underwent primary excision of the distal ulna with volar locking plate of the distal radius. Similar to our study, all fractures occurred in women.…”
Section: Discussionmentioning
confidence: 99%